The impact of decentralization on the speed of provision of administrative services in wartime conditions (Law and Safety, 2023)
The article focuses on the disclosure of the content of administrative services under the impact of decentralisation and the activities of relevant bodies aimed at ensuring human and civil rights and freedoms, interests of legal entities in wartime, and identifying factors affecting the speed of their provision. It has been noted that, in order to improve the quality and speed of administrative service provision in the context of war under the influence of decentralisation, the issue of decentralisation of powers to provide administrative services at the level of local self-government bodies is becoming particularly relevant, in particular through the instruments of delegation, transfer of powers and budget revenues from state bodies to local self-government bodies.It has been noted that the legal institution of administrative services is a system of relatively separate and interrelated legal provisions which regulate relations arising in the course of exercising subjective rights of an individual or a legal entity (at their request) in the course of public authority activities of an administrative body. Administrative services as part of public are provided by executive authorities and local self-government bodies. Their provision is related to the exercise of power.On the basis of the analysis of scholars’ scientific positions, the terms “public service”, “administrative and legal instrument”, “administrative service” have been studied. The factors affecting the speed of providing quality basic administrative services under the influence of decentralisation in the context of war have been identified, and the general prospects for the development of the administrative service delivery system have been determined, in particular: regulation of payment for administrative services, deregulation and administrative simplification to reduce the number of administrative services and simplify the procedures for providing specific services. The importance of information exchange between electronic registers, the possibility of using electronic services throughout the country, and optimising the distribution of powers between different levels of public administration has been emphasised.
Keywords: administrative and legal instrument; public services; administrative services; public service theory; decentralisation.